2020
DOI: 10.1177/1534508420937801
|View full text |Cite
|
Sign up to set email alerts
|

Addressing the Large Standard Error of Traditional CBM-R: Estimating the Conditional Standard Error of a Model-Based Estimate of CBM-R

Abstract: Curriculum-based measurement of oral reading fluency (CBM-R) is widely used across the country as a quick measure of reading proficiency that also serves as a good predictor of comprehension and overall reading achievement, but has several practical and technical inadequacies, including a large standard error of measurement (SEM). Reducing the SEM of CBM-R scores has positive implications for educators using these measures to screen or monitor student growth. The purpose of this study was to compare t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 11 publications
0
6
1
Order By: Relevance
“…In addition, the correlation between the latent intercept and slope factors for the CORE models were negative and moderate in magnitude, but were positive and small to moderate in magnitude for the traditional CBM-R models. These results may reflect of a ceiling effect, but that is not supported by the data; rather, these results suggest the model-based CORE scores are more sensitive to growth for students at risk of poor reading outcomes (i.e., lower fall WCPM scores), a finding that is supported by previous research that found increased precision (i.e., smaller conditional standard error of measurement) for CBM-R scores at/below the 25th percentile (Nese & Kamata, 2020a). This finding should be further examined by future research.…”
Section: Discussioncontrasting
confidence: 75%
See 2 more Smart Citations
“…In addition, the correlation between the latent intercept and slope factors for the CORE models were negative and moderate in magnitude, but were positive and small to moderate in magnitude for the traditional CBM-R models. These results may reflect of a ceiling effect, but that is not supported by the data; rather, these results suggest the model-based CORE scores are more sensitive to growth for students at risk of poor reading outcomes (i.e., lower fall WCPM scores), a finding that is supported by previous research that found increased precision (i.e., smaller conditional standard error of measurement) for CBM-R scores at/below the 25th percentile (Nese & Kamata, 2020a). This finding should be further examined by future research.…”
Section: Discussioncontrasting
confidence: 75%
“…CORE reshapes oral reading fluency and traditional CBM-R assessment by allowing group administration, more than one minute of reading, multiple passages, machine scoring, and WCPM scale scores. The benefits include reduced human administration cost and errors (Nese & Kamata, 2020b), and reduced standard error of measurement (Nese & Kamata, 2020a). The results of this study suggest increased measurement precision for the model-based CORE scores compared to traditional CBM-R, providing preliminary evidence that CORE can be used for consequential assessment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, research has shown that the use of shorter passages, in combination with advanced psychometric modeling, has the potential to reduce the standard error and increase the reliability of WCPM scores (Kara et al, 2020). A smaller standard error for CBM-R scores would provide educators with more accurate scores with which to monitor student CBM-R progress over time (Nese & Kamata, 2020), and thus increase the consequential validity of the decisions based on those scores.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional CBM-R scores are generally associated with large measurement error, or large SE (Ardoin & Christ, 2009; Christ & Silberglitt, 2007; Christ et al, 2012; Poncy et al, 2005), which can affect the interpretations and consequences of the assessment results as teachers use CBM-R fluency scores to screen for students at risk of poor reading outcomes and monitor student progress to inform instruction (Christ & Coolong-Chaffin, 2007). Along with a psychometric modeling approach (Kara, Kamata, Potgieter, & Nese, 2020; Potgieter, Kamata, & Kara, 2017), having students read several shorter passages may be part of a larger solution to reduce the large SE associated with traditional CBM-R fluency scores and increase score reliability (Nese & Kamata, 2020). Thus, in this study we explore whether shorter passages (25 to 85 words) read in their entirety function comparably to traditional CBM-R passages (about 250 words) read for 60 s.…”
Section: The Large Standard Error (Se) Of Traditional Cbm-r Scoresmentioning
confidence: 99%